Analisis Kemampuan Komunikasi Matematis Ditinjau Dari Gaya Belajar Siswa Kelas VIII SMPN 5 Kota Bima Tahun Ajaran 2021/2022 - Tara Rezika Aliffianti; Nani Kurniati; Nilza Humaira Salsabila; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe mathematical communication skills in terms of visual, auditory, and kinesthetic learning styles on the material of a two-variable linear equation system. The type of research is descriptive research. The research instrument are learning style questionnaire, a mathematical communication skill test, and an interview guide. Taking the subject in this study by purposive sampling, obtained 6 students of class VIII-1 SMPN 5 Bima City where 2 students with visual learning styles, 2 students with auditory learning styles, and 2 students with kinesthetic learning styles. The six students were given questions about mathematical communication skills tests and interviews. The results are mathematical communication skills of students with visual learning style is in the sufficient category, and students with auditory and kinesthetic learning styles had mathematical communication skills which are in less category. This is indicated by students with visual learning style who are able to fulfill the indicators of writing and mathematical expression but are not able to fulfill the indicators of drawing. Students with auditory learning style and kinesthetic learning style are not able to fulfill the indicators of writing, mathematical expression, and drawing.